Combined central retinal artery occlusion and anterior ischemic optic neuropathy as presenting signs of systemic lupus erythematosus - Saidane, R; Fendouli, I; El Matri, K; Hassairi, A; Chebil, A; El Matri, L (Journal francais d'ophtalmologie, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic auto-immune condition with systemic and ocular involvement. Ophthalmological findings are diverse and can involve all layers of the globe. Posterior segment manifestations can include lupus retinopathy, retinal vascular occlusions and lupus choroidopathy. We report here a rare case of central retinal artery occlusion (CRAO) associated with anterior ischemic optic neuropathy (AION) in a young female patient as presenting signs of SLE. In this case report, we highlight a very uncommon initial presentation of this severe systemic vasculitis. A multidisciplinary approach is required in order to prevent life-threatening vaso-occlusive complications.